2021
DOI: 10.1021/acs.analchem.1c00444
|View full text |Cite
|
Sign up to set email alerts
|

Target-Dependent Gating of Nanopores Integrated with H-Cell: Toward A General Platform for Photoelectrochemical Bioanalysis

Abstract: Herein we present a proof-of-concept study of target-dependent gating of nanopores for general photoelectrochemical (PEC) bioanalysis in an H-cell. The model system was constructed upon a left chamber containing ascorbic acid (AA), the antibody modified porous anodic alumina (AAO) membrane separator, and a right chamber placed with the three-electrode system. The sandwich immunocomplexation and the associated enzymatic generation of biocatalytic precipitation (BCP) in the AAO nanopores would regulate the diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…[31] In addition, from the perspective of input and output signals, another feature of this methodology is the transition from "electricity-electricity" to "light-electricity"; that is, reduced background could be achieved due to the separation and different energy form of the input signal (light) and the output one (electricity). [32][33][34][35] Given the rich light-matter interactions, much remains to be done to exploit the unknown effects and characteristics. However, due to the short development time, the study in this arena is still in its embryonic stage.…”
Section: Introductionmentioning
confidence: 99%
“…[31] In addition, from the perspective of input and output signals, another feature of this methodology is the transition from "electricity-electricity" to "light-electricity"; that is, reduced background could be achieved due to the separation and different energy form of the input signal (light) and the output one (electricity). [32][33][34][35] Given the rich light-matter interactions, much remains to be done to exploit the unknown effects and characteristics. However, due to the short development time, the study in this arena is still in its embryonic stage.…”
Section: Introductionmentioning
confidence: 99%
“…The general diagnosis of AMI in clinical practice requires the comprehensive consideration of an electrocardiogram and abnormal biomarker levels. Evidence from the scientific literature has revealed that cardiac biomarkers, e.g., myoglobin, B-type natriuretic peptide, heart-type fatty acid binding protein (h-FABP), and cardiac troponin I (cTnI), can provide a rapid diagnosis of AMI. However, detection of the extremely small variations in the concentrations of these biomarkers during the onset of AMI remains challenging, which limits accurate diagnosis. Several techniques have been proposed for the analysis of AMI biomarkers including fluorescence, , chemiluminescence, photothermal biosensing, , and electrochemical detection. Among these, advanced photoelectrochemical (PEC) bioanalysis enables the fusion of photodriven electrochemical responses with various biological recognition events to monitor physiological and pathological parameters, making it a promising and burgeoning technique in life science research. Currently, developing unique signal-on sensing mechanisms is a significant research branch in PEC bioanalysis due to their reduced background signals and high sensitivity.…”
mentioning
confidence: 99%
“…To support the PEC mode bioanalysis, a ZnInS–FTO photoanode , was prepared, and its morphology was characterized by SEM. As shown in Figure A, the ZnInS film exhibited a three-dimensional (3D) nanowall network grown vertically on the FTO surface, with the nanosheet thickness of ca.…”
Section: Resultsmentioning
confidence: 99%